The Expression of Self and Grief in the Nineteenth Century: An Analysis through Distant Readings. Issue 1 (19th April 2021) - Monzingo, Elizabeth; Shanahan, Daniel
Abstract : When writing about grief, Peter N. Stearns and Mark Knapp ('Historical Perspectives on Grief', in The Emotions: Social, Cultural and Biological Dimensions, ed. Rom Harré and W. Gerrod Parrot (London: Sage Publications, 1996): 138) speculate that '[i]n contrast to eighteenth-century songs about death, which were set in the artificial pastoral world of shepherds and written in the third person, Victorian grief songs were personal and immediate'. Inspired by this claim, we investigated the usage of pronouns, as well as topics surrounding grief, in ballads taken from broadsides in the nineteenth century. We found that the use of first-person pronouns increases over the nineteenth century, and that this was not a linear trend; there were sharp increases in the usage of first-person pronouns beginning in 1815, which leveled off in the third quarter of the century. Additionally, we examined the usage of lyrical topics about death, grieving, negatively valenced emotion and sadness, and asked whether such topics correlated with the increased usage of first-person pronouns. We found that there was not a strong correlation with the usage of pronouns and such topics, though there was a small correlation between the usage of such pronouns and sadness and a stronger positive correlation between a focus on the present and positively valenced emotion. These findings suggest that first-person pronouns are not reliable indicators of lyrical topics surrounding grief, or vice-versa. Using personal pronouns as a measure of intimacy, we conclude that songs written in the beginning of the nineteenth century did see a rise in intimacy in song lyrics. However, this increase does not appear to be tied to songs about grief, specifically. Despite the existence of many personal grief songs in the Victorian period, our distant reading reveals linguistic trends and interrelations that challenge the intuition that nineteenth-century grief songs were more personal than earlier ones.